Ciência e pseudociência na concepção dos alunos dos cursos de Ciências Biológicas da UFSCar campus Sorocaba - Ribeiro, Priscila Cleto (Universidade Federal de São Carlos, 2021)
Science is the best way that humanity has developed to build knowledge. It has its foundations among the great Greek philosophers and it is in constant process of development. The foundation stone of Science is the falsifiability in which the knowledge generated by science is constantly tested in light of new evidence, which can either corroborate or refute previous hypotheses. This brings solidity to scientific knowledge, yielding a relevant authority of Science for society. In turn, Pseudoscience is a set of irrefutable dogmas that dressed up with supposed scientific authority, claims it has the same relevance in the process of knowledge construction as Science. This research aimed to verify the science conception and pseudoscientific bias of students in the three Biological Sciences courses in the Sorocaba campus of Universidade Federal de São Carlos– UFSCar, as well as how these concepts are distributed along the students’ training years and how they are present in each of the courses. This study was accomplished through the online application of a quantitative and qualitative questionnaire joined by 90 students out of a total of 542 enrolled in the three Biological Sciences courses (Bachelor and Licentiate degrees). It was verified the effective deconstruction of pseudoscientific conceptions throughout the formative years but also the considerable amount of students who continue to accept pseudosciences based on belief systems. In addition, we found that schools represent the main mean by which people have their first contact with Science. Therefore, although education has moved towards greater scientific enlightenment, there is still a long path ahead.
Science and pseudoscience in the conception of students from the undergraduate courses of Biology at UFSCar Sorocaba
Keywords: Ensino de ciências; Ciência básica; Science teaching; Basic science; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO